Tort Law and Medical Malpractice Insurance Premiums - Meredith L. Kilgore; Michael A. Morrisey; Leonard J. Nelson (SAGE Publishing, 2006)
This paper estimated the effects of tort law and insurer investment returns on physician malpractice insurance premiums. Data were collected on tort law from 1991 through 2004, and multivariate regression models, including fixed effects for state and year, were used to estimate the effect of changes in tort law on medical malpractice premiums. The premium consequences of national policy changes were simulated. The analysis found that the introduction of a new damage cap lowered malpractice premiums for internal medicine, general surgery, and obstetrics/gynecology by 17.3%, 20.7%, and 25.5%, respectively. Lowering damage caps by $100,000 reduced premiums by 4%. Statutes of repose also resulted in lower premiums. No other tort law changes had the effect of lowering premiums. Simulation results indicate that a national cap of $250,000 on awards for noneconomic damages in all states would imply premium savings of $16.9 billion. Extending a $250,000 cap to all states that do not currently have them would save $1.4 billion annually, or about 8% of the total. A negative effect on malpractice premiums was found for the Dow Jones industrial average, but not for bond prices; effects of the Nasdaq index were not significant for internal medicine, but were marginally significant for surgery and obstetrics premiums.